Transducer of Pressure with a Frequency Output - Osadchuk, V. S.; Osadchuk, A. V. (Elektronika ir Elektrotechnika, 2006)
In the given article operation research of a pressure transducer are presented on the basis of reactive properties of transistors. The analytical dependences of function converting and equation of sensitivity are obtained. The theoretical and experimental research have shown, that the sensitivity of a designed transducer of pressure makes 450 Hz/kPa. Ill. 3, bibl. 10 (in English; summaries in English, Russian and Lithuanian).